2013
DOI: 10.3822/ijtmb.v6i3.199
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Injury-forced Work Reduction for Massage Therapists and Bodywork Practitioners†

Abstract: Background: Injury-forced work reduction (IFWR) has been acknowledged as an all-toocommon occurrence for massage therapists and bodywork practitioners (M & Bs). However, little prior research has specifically investigated demographic, work attitude, and perceptual correlates of IFWR among M & Bs.Purpose: To test two hypotheses, H1 and H2. H1 is that the accumulated cost variables set ( e.g., accumulated costs, continuing education costs) will account for a significant amount of IFWR variance beyond control/dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…A study of clinicians showed that, on average, physicians consider CAM to be moderately effective, and 23.3% of them consider it to be an effective method of treatment [12] and would recommend it to their patients. The most common reasons for recommendation are to relax musculoskeletal pain, chronic disease, and nerve pain [13][14][15]. There is a worldwide shift in the attitude towards CAM due to its use as secondary care and integration into mainstream medical care [16].…”
Section: Introductionmentioning
confidence: 99%
“…A study of clinicians showed that, on average, physicians consider CAM to be moderately effective, and 23.3% of them consider it to be an effective method of treatment [12] and would recommend it to their patients. The most common reasons for recommendation are to relax musculoskeletal pain, chronic disease, and nerve pain [13][14][15]. There is a worldwide shift in the attitude towards CAM due to its use as secondary care and integration into mainstream medical care [16].…”
Section: Introductionmentioning
confidence: 99%
“…2 This relates to recognized occupational risk factors for increased musculoskeletal injury among MTs including work duration, amount of daily client contact, lack of self-care practices, and fatigue. 6,7,10 In addition, employment in massage therapy has many of the attributes of precarious employment, 11,12 given the lower gross wages, 2 high rate of underemployment (persons working part-time but are seeking full-time employment), 1,13 low employee benefits (ie, sick leave, paid time off, insurance), 1 high risk of sexual harassment at work, 14 and the large proportion of MTs employed as independent contractors. 1,2 Precarious work is directly associated with lower job satisfaction, psychological stress, and higher work-related injury rates.…”
mentioning
confidence: 99%
“…For massage therapists, while average hourly rates charged per customer are relatively high ($72/h), 1 earned hourly rates vary widely across the industry 1 with an adjusted gross earned hourly rate of $21.41 for all MTs 2 . This relates to recognized occupational risk factors for increased musculoskeletal injury among MTs including work duration, amount of daily client contact, lack of self-care practices, and fatigue 6,7,10 . In addition, employment in massage therapy has many of the attributes of precarious employment, 11,12 given the lower gross wages, 2 high rate of underemployment (persons working part-time but are seeking full-time employment), 1,13 low employee benefits (ie, sick leave, paid time off, insurance), 1 high risk of sexual harassment at work, 14 and the large proportion of MTs employed as independent contractors 1,2 .…”
mentioning
confidence: 99%